THE EFFECTIVENESS OF ADDING DYNAMIC STRETCHING EXERCISES TO BALANCE STRATEGY EXERCISES IN IMPROVING BALANCE IN THE ELDERLY - Govinda Vittala; Cahyo Setiawan (P3M Universitas 'Aisyiyah Surakarta, 2023)
Background: As we get older, the ability to balance the body is decreased, which will cause health problems because the risk of falling increases. The effective exercise is needed for the elderly to maintain and improve their ability to balance the body. Aims: This study aims to determine the effectiveness of adding dynamic stretching exercise to the balance strategy exercise in improving balance in the elderly. Participants and Methods: This study was a randomized control trial with a total number of 24 elderly as subjects who were selected based on inclusion and exclusion criteria which were then divided into 2 groups. Group 1 was given dynamic stretching exercise and balance strategy exercise, and group 2 was given balance strategy exercise only. Exercise is done 3 times a week for 6 weeks. Results: The results of data analysis using the Paired Sample T-test showed that the results of p<0.05 indicated that there was a significant increase in the BBS score before and after exercise. The Independent T-test on the BBS score after exercise showed a p<0.05 which indicated that there was a significant difference in the post-test BBS scores between groups 1 and 2, where group 1 experienced a higher increasement of BBS score in balance compared to group 2. Conclusion: Based on the results of data analysis, the addition of dynamic stretching exercise to balance strategy exercise is more effective in improving balance in the elderly compared to balance strategy exercise only.